Technology paternalism: Development and validation of a measurement scale - Martin Rochi; Philipp A. Rauschnabel; Karl-Heinz Renner; Björn S. Ivens (Psychology & Marketing, 2024)
As technologies become smarter, they tend to protect their users, much like parents protect their children. However, caring too much about a user can lead to technology paternalism, a construct that is becoming increasingly relevant with the advent of smart technologies. Nonetheless, very little is known about what technology paternalism is or how it can be measured. The authors applied established procedures from scale development methodology followed by quantitative measurement to present and validate a three-factor scale (limiting, overruling, and welfare). The approach offers first empirical evidence linking technology paternalism to associated concepts, showing that it correlates as expected with established constructs in the literature on technology acceptance. This study contributes to the literature by uncovering a construct of interest to a critical discussion of technology paternalism and by providing a measurement tool that can be used by researchers, policy makers, and managers.
Keywords: 650; paternalism; scale development; smart technologies; technology acceptance; technology paternalism; technology resistance